Structural templating in a non-planar phthalocyanine using single crystal copper iodide - Ramadan,AJ; Rochford,LA; Keeble,DS; Ryan,MP; Heutz,SE; Jones,TS (Advanced Materials Interfaces, 2015)
Solution-grown copper iodide crystals are used as substrates for the templated growth of the nonplanar vanadyl phthalocyanine using organic molecular beam deposition. Structural characterization reveals a single molecular orientation produced by the (111) Miller plane of the copper iodide crystals. These fundamental measurements show the importance of morphology and structure in templating interactions for organic electronics applications.